Capacity Building of Facilitators in the Context of Pastoral Ministry at St. Joseph Church Tanjung Balai Karimun - Jesica Cindini br Sembiring (Lembaga Pengembangan Kinerja Dosen, 2025)
Pastoral ministry is at the core of the life of the Church which requires the active and qualified involvement of its implementers, especially facilitators. At St. Joseph Tanjung Balai Karimun Church, the role of facilitators is very important in reviving the Ecclesiastical Base Community (KBG) as the main means of fostering the faith of the people. However, the limited number and capacity of facilitators are obstacles in supporting the effectiveness of pastoral ministry. This community service activity aims to increase the capacity of facilitators through training that focuses on developing communication competencies, faith mentoring, and pastoral leadership. The method used was observation and participatory training for three months, with periodic evaluation through reflection with participants. The results of the activity showed a significant increase in confidence, empathic communication skills, and the effectiveness of facilitators in managing group dynamics. In addition, the KBG meeting became more lively and participatory. Pastorally, this activity shows that strengthening the capacity of facilitators is not only a technical solution, but also a long-term strategy in building an independent, synodal and empowered Church. This activity is expected to be a model for other parishes in developing pastoral services that are contextual and relevant to the lives of today's people.